The value of multi-parameters MRI based on amide proton transfer imaging in evaluating the efficacy of concurrent radiochemotherapy for locally advanced cervical cancer - Yang, Chongshuang; Abu Hassan, Hasyma; Omar, Nur Farhayu; Soo, Tze Hui; Yahaya, Ahmad Shuib; Shi, Tianliang; Qin, Zhihong; Wu, Min; Yang, Changfu (Elsevier Inc., 2025)
Objective: To evaluate the utility of multi-parametric magnetic resonance imaging (MRI) based on amide proton transfer (APT) imaging in assessing the efficacy of concurrent chemoradiotherapy (CCRT) for locally advanced cervical cancer (CC). Materials and methods: We retrospectively analyzed clinical and imaging data from pathologically confirmed CC patients treated at our hospital between January 2020 and May 2025. All patients underwent conventional MRI, APT imaging, and dynamic contrast-enhanced MRI (DCE-MRI) prior to treatment. Apparent diffusion coefficient (ADC) values, APT values, and semi-quantitative parameters from DCE-MRI were measured. Treatment response following CCRT was evaluated based on the Response Evaluation Criteria in Solid Tumors (RECIST). Complete remission (CR) and partial remission (PR) were classified as the remission group (RG), while stable disease (SD) and progressive disease (PD) were grouped as the non-remission group (NRG). Differences in APT values, ADC values, and semi-quantitative parameters of DCE-MRI between RG and NRG were analyzed. Receiver operating characteristic (ROC) curves were used to assess the sensitivity, specificity, and area under the curve (AUC) of APT, ADC, semi-quantitative parameters of DCE-MRI, and their combinations in predicting CCRT response. The Delong test was used for statistical comparison of AUCs. Results: A total of 43 patients were included, with 5 (11.63 %) achieving CR, 31 (72.09 %) achieving PR, 5 (11.63 %) classified as SD, and 2 (4.65 %) as PD, resulting in a local control rate of 95.35 %. The APT value in the RG was significantly lower than in the NRG (3.13 % ± 0.24 % vs. 3.36 % ± 0.16 %, P = 0.02), while the ADC value was significantly higher [(0.89 ± 0.11) × 10−3 mm2/s vs. (0.80 ± 0.07) × 10−3 mm2/s, P = 0.034]. The NRG showed significantly higher values in wash-in rate (WIR) compared to the RG (P = 0.035). The AUC of APT in differentiating RG from NRG was higher than that of ADC and WIR, but the differences were not statistically significant (P > 0.05). Moreover, the combined use of APT, ADC, and WIR increased the AUC to 0.893, which was significantly higher than that of WIR alone (P = 0.024). Conclusion: Multi-parametric MRI based on APT imaging holds promise for predicting CCRT outcomes in locally advanced CC. The combination of APT, ADC, and WIR improves diagnostic accuracy compared to individual parameters, offering a potential non-invasive tool for guiding clinical management after CCRT.